1999
DOI: 10.1007/s11818-999-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Dream content of patients with sleep apnea

Abstract: ZusammenfassungPrevious research has shown that external stimuli were often incorporated into the dream to some extend. The aim of the present study was to investigate whether the internal stimulus sleep apnea is also incorporated into dreams. Findings showed, however, that direct incorporation occurs very seldom. On the other hand, arousals accompanying sleep apneas seem to interfere with dream formation since a marked reduction of dream bizarreness is related to high RDI (respiratory disturbance index). Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 9 publications
0
28
1
2
Order By: Relevance
“…Dream recall frequency in patients with sleep apnea was reduced in this study, which is in contrast to previous findings [19,20]. Schredl [19] and Schredl et al [20] found a heightened dream recall frequency in these patients compared to healthy controls, which was partly explained by the frequency of nocturnal awakenings (higher in the sleep apnea group) and the amount of daytime stress.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Dream recall frequency in patients with sleep apnea was reduced in this study, which is in contrast to previous findings [19,20]. Schredl [19] and Schredl et al [20] found a heightened dream recall frequency in these patients compared to healthy controls, which was partly explained by the frequency of nocturnal awakenings (higher in the sleep apnea group) and the amount of daytime stress.…”
Section: Discussioncontrasting
confidence: 99%
“…Schredl [19] and Schredl et al [20] found a heightened dream recall frequency in these patients compared to healthy controls, which was partly explained by the frequency of nocturnal awakenings (higher in the sleep apnea group) and the amount of daytime stress. To explain these contradictory findings, it will be necessary to measure various factors such as personality dimensions, interest in dreams, creativity, and sleep behavior that have been found to be related to dream recall in persons without sleep disorders (cf.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Schredl et al found an elevated dream-recall frequency in patients with sleep-disordered breathing (SDB) without any correlation, however, with the frequency of nocturnal awakenings [86]. A strong negative correlation was found between the frequency of respiratory events and dream bizarreness, suggesting that apnoea-induced arousals may interrupt the (REM-)dream process.…”
Section: Sleep-disordered Breathingmentioning
confidence: 99%